Environmental contamination : health risks and ecological restoration - Wong, Ming H. (Taylor & Francis, 2013)
"Drawn from presentations made during the Croucher Advanced Study Institute workshop held in 2010, this volume covers all the fundamentals necessary for contaminated site assessment and remediation. It discusses historical and emerging contaminants, human health, risk assessment and bioremediation. It contains numerous case studies, many of them from the Asia-Pacific region, that look at the effects of rapid industrialization. It also examines both historical and emerging contaminants such as persistent organic pollutants and electronic waste"--